ANALISIS PENYERAPAN TENAGA KERJA SEKTOR PARIWISATA DI JAWA BARAT - andang yoga utama; rifki khoirudin (Universitas Lancang Kuning, 2021)
This study aims to determine the impact of tourism in Jawa Barat on employment in the tourism sector from 2014 to 2018. This study uses secondary data in the form of panel data in the province of Jawa Barat. The variables used are the number of tourist visits, hotels, restaurants and tourist objects. The results showed that tourist visits did not have a significant effect on employment in the tourism industry, hotels had no significant effect on emlpoyment in the tourism industry, restaurants had a positive and significant effect on empolyment in the tourism industry. In the tourism industry, tourist objects has a positive and significant impact. Absorbing labor in the tourism sector. The value of R² in this study is 0.962321, this means that the number of tourist visits, the number of hotels, the number of restaurants, and the number of tourist objects can explain the dependent variable of employment by 96.23%, while 3.77% is explained by other variables outside the model.